Hydroxysafflor Yellow A: A Promising Therapeutic Agent for a Broad Spectrum of Diseases. (25th September 2018) - Ao, Hui; Feng, Wuwen; Peng, Cheng
Abstract : Hydroxysafflor yellow A (HSYA) is one of the major bioactive and water-soluble compounds isolated from Carthami Flos, the flower of safflower ( Carthamus tinctorius L.). As a natural pigment with favorable medical use, HSYA has gained extensive attention due to broad and effective pharmacological activities since first isolation in 1993. In clinic, the safflor yellow injection which mainly contains about 80% HSYA was approved by the China State Food and Drug Administration and used to treat cardiac diseases such as angina pectoris. In basic pharmacology, HSYA has been proved to exhibit a broad spectrum of biological effects that include, but not limited to, cardiovascular effect, neuroprotection, liver and lung protection, antitumor activity, metabolism regulation, and endothelium cell protection. Although a great number of studies have been carried out to prove the pharmacological effects and corresponding mechanisms of HYSA, a systemic review of HYSA has not yet been seen. Here, we provide a comprehensive summarization of the pharmacological effects of HYSA. Together with special attention to mechanisms of actions, this review can serve as the basis for further researches and developments of this medicinal compound.